Jobless Citizens : Political Engagement of the Young Unemployed - Giugni, Marco; Lorenzini, Jasmine (Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2017)
This book examines patterns of political engagement of long-term unemployed youth. The authors show how unemployment affects the personal, social, and political life of young people. Focusing on the case of Geneva in Switzerland, the study shows the importance of socioeconomic, relational, psychological, and institutional resources for the political engagement of unemployed youth. The book shows specifically how the relationship between unemployment and the political engagement of unemployed youth is mediated by a number of factors: their socioeconomic status and more generally their individual background, their level of deprivation and the associated degree of subjective well-being; the social capital that unemployed youth draw from involvement in voluntary associations and interpersonal networks and relations, and the political learning stemming from interactions with welfare institutions and their perception of such interactions. Students and scholars in areas including Sociology, Political Science, Economics, Youth Studies and Social Policy will find this study of interest.
Keywords: Social sciences.; Labor economics.; Political sociology.; Industrial sociology.; Social policy.; elektronické knihy; electronic books